2010
DOI: 10.1111/j.1365-2141.2010.08368.x
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH1 PEST domain mutation is an adverse prognostic factor in B‐CLL

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 9 publications
4
83
0
Order By: Relevance
“…13 Recently, using next-generation sequencing technologies, different groups discovered that 4% of CLL patients also harbor NOTCH1 mutations ( Table 1), indicating that mutations could be one of the mechanisms explaining NOTCH activation in this disease. [3][4][5]14 Different to T-ALL, the mutations almost exclusively occur in exon 34 and usually generate a premature stop codon resulting in a constitutively active and more stable NOTCH1 protein lacking the Cterminal PEST domain. A recurrent CT deletion (p.P2515fs4) was found in around 80% of NOTCH1 mutation positive CLL cases, and a PCR based strategy has been designed for its rapid detection.…”
Section: 2mentioning
confidence: 99%
“…13 Recently, using next-generation sequencing technologies, different groups discovered that 4% of CLL patients also harbor NOTCH1 mutations ( Table 1), indicating that mutations could be one of the mechanisms explaining NOTCH activation in this disease. [3][4][5]14 Different to T-ALL, the mutations almost exclusively occur in exon 34 and usually generate a premature stop codon resulting in a constitutively active and more stable NOTCH1 protein lacking the Cterminal PEST domain. A recurrent CT deletion (p.P2515fs4) was found in around 80% of NOTCH1 mutation positive CLL cases, and a PCR based strategy has been designed for its rapid detection.…”
Section: 2mentioning
confidence: 99%
“…5,6 The prevalence of NOTCH1 mutations increases with disease aggressiveness. 5 At diagnosis, NOTCH1 mutations show an adverse impact on outcome, confirmed in at least four series, [4][5][6][7] and act independently of other clinico-biological features, including TP53 disruption. 7 Among CLL cytogenetic subgroups, NOTCH1 mutations are distributed in a mutually exclusive fashion with TP53 disruption and are enriched in CLL carrying +12, where they recur in approximately 25% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 The NOTCH1 gene has been shown to have an essential biological role in hematopoiesis. 3 Following the pivotal study that identified NOTCH1 mutations in CLL and provided initial evidence on the unfavorable clinical outcome associated with NOTCH1 alterations, 4 two independent studies of the CLL coding genome have recently identified activating mutations of the NOTCH1 gene in approximately 10% of CLL at diagnosis. 5,6 The prevalence of NOTCH1 mutations increases with disease aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…In some series, mutations of NOTCH1 and FBXW7 are associated with the presence of trisomy 12 and the nonmutated status of the hypervariable regions of immunoglobulin genes. [65][66][67][68] MYD88 is mutated in CLL, the most frequent mutations being L265P mutation, as in B-cell lymphoma. 69 MYD88 missense mutations are activator type mutations that result in the constitutive activation of the transcription factors STAT3 and NFkB.…”
Section: Other Novel Mutations In Lymphomasmentioning
confidence: 99%